Konflik Batin Tokoh Utama dalam Novel Rumah untuk Alie Karya Lenn Liu: Perspektif Psikoanalisis Sigmund Freud - Yessy Assyamu Novianti; Moh. Ahsan Shohifur Rizal (STIKes Ibnu Sina Ajibarang, 2026)
Research on the inner conflict of the main character in Lenn Liu novel Rumah untuk Alie is important because literary works not only present stories, but also depict the complex psychological reality of humans. This study aims to describe the inner conflict of the main character in Lenn Liu novel Rumah untuk Alie using Sigmund Freud psychoanalytic theory. The method used in this study is descriptive qualitative with data collection techniques in the form of reading and note-taking. The results of the study indicate that the inner conflict of the main character in Lenn Liu novel Rumah untuk Alie includes three personality structures according to Sigmund Freud psychoanalytic theory, namely the id, ego, and superego. This conflict is dominated by the id aspect which is characterized by a strong drive to obtain affection and acceptance that is not fulfilled. In addition, the main character also shows various self-defense mechanisms in response to the psychological pressure he experiences. The findings of this study indicate that the inner conflict of the main character in Lenn Liu novel Rumah untuk Alie is closely related to the unfulfilled emotional needs, especially affection and acceptance in the family environment. This condition gives rise to psychological pressure that drives the main character to use various self-defense mechanisms as a form of self-protection.